Strength of concrete with wood ash and waste glass as partial replacement materials. Issue 1 (June 2020) - Thomas, Anu V; Ramaswamy, K P; Nair, Adarsh; Padmanabhan, R; Isac, Tom K; Anilkumar, Vishnu
Abstract: This paper discusses a study on the use of wood ash as partial replacement of cement and waste glass as partial replacement of fine aggregate in concrete. Wood ash was used to replace cement at 5% and 10% and waste glass was used to replace fine aggregate at 10% and 15%. When wood ash was added to concrete, the compressive strength of concrete was found to reduce marginally with respect to the reference mix and the optimal value of compressive strength was obtained at 5% replacement. Addition of waste glass to replace fine aggregate resulted in marginal reduction of compressive strength of concrete at 10% replacement. However, a drastic reduction in compressive strength was observed at 15% replacement level of waste glass. Replacing 5% of cement with wood ash and 10% of fine aggregate with waste glass yielded satisfactory results and thereby at these replacement levels, wood ash and waste glass can be used as replacement materials in concrete. Incorporating the waste materials in concrete will be an efficient and effective way to dispose these materials and will result in lower consumption of natural materials in the manufacturing process of concrete thereby resulting in an environment friendly and cheaper concrete.